The magnetic, electrical transport and magnetoresistance properties of epitaxial La0.7Sr0.3Mn1-xFexO3 (x = 0-0.20) thin films prepared by pulsed laser deposition - Huang, Q. (2014)
10.1088/0953-8984/13/18/312